Forward link quality estimation in VANETs for sender-oriented alert messages broadcast. (December 2015) - Rehman, Osama M. Hussain; Bourdoucen, Hadj; Ould-Khaoua, Mohamed
Abstract: Messages broadcasting protocols over vehicular ad hoc networks (VANETs) have strong potentials in enhancing road traffic safety and management including the reduction of high speed road accidents and chaotic traffic congestions. Reliable and timely reception of broadcast messages are two prime objectives in the development of safety alert messaging protocols in VANETs. This paper proposes a new sender-oriented broadcasting scheme for alert messages dissemination in VANETs, referred to as bi-directional stable communication (BDSC) protocol. A link quality estimation algorithm is exploited to recurrently quantify the quality of forward communication links. The proposed BDSC protocol improves the selection of the next relay nodes in multi-hop propagation environments, such as that formed by a platoon of vehicles. This results in achieving reachability improvement of the disseminated alert messages over densely populated vehicular network with high data traffic generation rates. Indeed, a quantitative analysis through extensive simulations reveal that the proposed protocol achieves higher reachability compared to existing sender-oriented relay selection protocols. Our study also assesses the impact of vehicles׳ relative mobility speed difference on VANET performance, specifically with respect to the end-to-end delay. Owing to the suggested BDSC protocol efficient relay node selection mechanism, our results show that the BDSC protocol achieves lower end-to-end delays compared to those exhibited by its sender-oriented counterparts as the maximum relative speed difference among traveling cars increases.